Development of Constructivist Theory of Mind from Middle Childhood to Early Adulthood and Its Relation to Social Cognition and Behavior - Weimer, Amy A. (J Exp Child Psychol, 2016)
Two studies examined the development of constructivist theory of mind (ToM) during late childhood and early adolescence. In Study 1 a new measure was developed to assess participants’ understanding of the interpretive and constructive processes embedded in memory, comprehension, attention, comparison, planning, and inference. Using this measure, Study 2 tested a mediational model in which prosocial reasoning about conflict mediated the relation between constructivist ToM and behavior problems in high school. Results showed that the onset of constructivist ToM occurs between late childhood and early adolescence, and that adolescents who have more advanced constructivist ToM have more prosocial reasoning about conflict, which in turn mediated the relation with fewer serious behavior problems in high school, after controlling for academic performance and sex. In both studies, females showed more advanced constructivist ToM than males in high school.